Hamstring injuries in England and Wales elite men's domestic cricket from 2010 to 2019. Issue 6 (June 2022) - Goggins, Luke; Langley, Ben; Griffin, Steve; Peirce, Nicholas; McKay, Carly; Stokes, Keith; Williams, Sean
Abstract: Objectives: Describe hamstring injury incidence across competition formats, activity at time of injury, and time of season, facilitating the identification of injury risk factors in elite men's senior First-Class County Cricket. Design: Prospective cohort. Methods: Hamstring time loss injury incidence (between format, activity, and time of season) calculated for elite men's senior First-Class County Cricket seasons 2010 to 2019. Results: The diagnosis with the highest seasonal incidence was 'Biceps femoris strain grade 1–2' (2.5 injuries/100 players). Hamstring injury incidence was highest in One-Day cricket (mean 27.2 injuries/1000 team days). Running between wickets when batting was the activity associated with the highest incidence in the shorter competition formats (8.4 and 4.8 injuries/1000 team days for One-Day and T20, respectively). Bowling delivery stride or follow through was the activity with the highest incidence for longer multi-day Test format (mean 2.3 injuries/1000 team days), although similar incidence was observed across all formats for this activity. Most injuries were sustained at the start of the season (April; 22.7 injuries/1000 team days), with significantly fewer injuries at end of the season (September; 4.1 injuries/1000 team days). Conclusions: Similar bowling injury incidence across formats suggests hamstring injury risk is associated more with the activity itself, whereas injury risk when batting was susceptible to changes in match intensity. The notably higher (albeit non-significant) incidence in April may allude to a lack of preparedness to meet the physical demands of the start of the season. The findings have practical relevance for practitioners, identifying potential opportunities for preventative strategies.